Um cântico para a ciência: utilizando a ficção científica para analisar a ciência durante a Guerra Fria - Santos, Gabriel Broisler (2024)
This dissertation proposes to study the role of science fiction works in analyzing different perspectives when viewing science from a given period. The selected work, A Canticle for Leibowitz, by Walter M. Miller Jr., was published at the turn of the 1950s to 1960s, that is, a period in which the Cold War, a political conflict between the United States and the Soviet Union, reached its peak. Starting from this period contextualization with an emphasis on the popularization of works in the science fiction literary genre and understanding the public's relationship with science at the time, one can highlight the feelings of hope linked to significant technological advances and the fear related to the development of nuclear war power. Furthermore, the presentation of the work structure, with emphasis on excerpts in which the author draws parallels or criticisms to the historical period of the book publication, complements the contextualization and enhances the possibility of reflection based on this comparison